Thar She Bursts: Reducing Confusion Reduces Bubbles - Kirchler, Michael; Huber, Jürgen; Stöckl, Thomas (American Economic Review, 2012)
To explore why bubbles frequently emerge in the experimental asset market model of Smith, Suchanek, and Williams (1988), we vary the fundamental value process (constant or declining) and the cash– to–asset value ratio (constant or increasing). We observe high mispricing in treatments with a declining fundamental value, while overvaluation emerges when coupled with an increasing C/A ratio. A questionnaire reveals that the declining fundamental value process confuses subjects, as they expect the fundamental value to stay constant. Running the experiment with a different context (“stocks of a depletable gold mine” instead of “stocks”) significantly reduces mispricing and overvaluation as it reduces confusion. (JEL C91, D14, G11, G12)